2016
DOI: 10.1111/gbi.12182
|View full text |Cite
|
Sign up to set email alerts
|

Oceanic oxygenation events in the anoxic Ediacaran ocean

Abstract: The ocean-atmosphere system is typically envisioned to have gone through a unidirectional oxygenation with significant oxygen increases in the earliest (ca. 635 Ma), middle (ca. 580 Ma), or late (ca. 560 Ma) Ediacaran Period. However, temporally discontinuous geochemical data and the patchy metazoan fossil record have been inadequate to chart the details of Ediacaran ocean oxygenation, raising fundamental debates about the timing of ocean oxygenation, its purported unidirectional rise, and its causal relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
202
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(227 citation statements)
references
References 82 publications
(172 reference statements)
23
202
1
1
Order By: Relevance
“…A recent compilation of Mo isotope data for euxinic black shales also reveals that significant oscillations in ocean redox conditions, and hence the seawater Mo inventory, may have occurred across the Precambrian-Phanerozoic transition before the advent of permanent widespread ocean oxygenation (Dahl et al, 2010;Kendall et al, 2015a;Sahoo et al, 2016). This view adds a new dimension to existing evidence for predominantly ferruginous deep ocean conditions in the Proterozoic (e.g.…”
Section: A C C E P T E Dmentioning
confidence: 84%
See 1 more Smart Citation
“…A recent compilation of Mo isotope data for euxinic black shales also reveals that significant oscillations in ocean redox conditions, and hence the seawater Mo inventory, may have occurred across the Precambrian-Phanerozoic transition before the advent of permanent widespread ocean oxygenation (Dahl et al, 2010;Kendall et al, 2015a;Sahoo et al, 2016). This view adds a new dimension to existing evidence for predominantly ferruginous deep ocean conditions in the Proterozoic (e.g.…”
Section: A C C E P T E Dmentioning
confidence: 84%
“…Following increasing oxygenation in late Neoproterozoic (Canfield et al, 2007;Scott et al, 2008;Sahoo et al, 2012;Lyons et al, 2014aSahoo et al, 2016), these sulfide complexes would have become less abundant, resulting in greater availability of Cd, Cu, and Zn. Under more oxic conditions first observed in the Cryogenian and continuing to develop into the Cambrian-Ordovician Sperling et al, 2015;Sahoo et al, 2016), the models of Saito et al (2003) indicated that Fe and Mn concentrations in seawater would have been drawn down to modern levels as the result of oxide mineral precipitation. This would have presented a challenge for many microbial clades, as Fe is the most common metal co-factor for both prokaryotes and eukaryotes (Dupont et al, 2010).…”
mentioning
confidence: 99%
“…Given the growing geochemical evidence for dynamic fluctuations in Neoproterozoic ocean redox conditions extending back to ca. 800 Ma (e.g., Sahoo et al, 2012Sahoo et al, , 2016Planavsky et al, 2014;Kendall et al, 2015;Sperling et al, 2015;Thomson et al, 2015;Cole et al, 2016;Turner and Bekker, 2016;Kuznetsov et al, 2017), the boundary between stages 3 and 4 may potentially shift back in time with new Re data. We also note the general absence of high Re enrichments (like those observed in the Late Ediacaran, Early Cambrian (>535 Ma), and Late Phanerozoic ORM) during the early Paleozoic (535-375 Ma).…”
Section: Temporal Trends In Re Concentrationsmentioning
confidence: 99%
“…While Re data from the Upper Velkerri and Touirist formations may potentially reflect transiently oxygenated marine conditions, the extent to which these data represent spatiotemporal variations in the midProterozoic atmosphere-ocean redox state remains to be tested with higher-resolution Re data for stage 3. Given recent trace element evidence for fluctuating redox conditions in the Neoproterozoic (e.g., Sahoo et al, 2012Sahoo et al, , 2016Planavsky et al, 2014;Kendall et al, 2015;Sperling et al, 2015;Thomson et al, 2015;Cole et al, 2016), transient episodes of broader ocean oxygenation in the Mesoproterozoic may be part of a dynamic, longer-term trend of protracted oxygenation-one characterized by significant temporal oscillations in atmosphere-ocean O 2 levels likely around still low baselines, which extended into the Neoproterozoic and early Paleozoic.…”
Section: Constraints On the Extent Of Mid-proterozoic Ocean Anoxiamentioning
confidence: 99%
“…Considering that oxygen was available, at least periodically, in the overlying water (Hood & Wallace 2014;Wood et al 2015;Cui et al 2016;Sahoo et al 2016), the upper surface of Ediacaran organisms is likely to have been adapted for oxygen uptake. Oxygen transport could have occurred within a diploblastic Ediacaran animal by diffusion through the mesenchyme, which could also have stored oxygen during periods of hypoxia, as demonstrated in the mesoglea of modern scyphomedusae (Thuesen et al 2005;Pitt et al 2013).…”
Section: Chemosynthetic Feeding Modes In Ediacaran Organismsmentioning
confidence: 99%